203k views
3 votes
Help me solve this please​

Help me solve this please​-example-1
User Logan H
by
5.0k points

2 Answers

5 votes

6/3=2

Explanation:

I know because 2×3=6 so 6/3 would have to equal 2.

User Laurance
by
5.5k points
3 votes

Answer:

x= -6

Explanation:

First, you would write down the equation how it is shown first.

1) -x/3=2

Second, you would naturally multiply both sides by -3. To solve the equation, you need to use the inverse operation in the inverted order of PEMDAS. (Parentheses, exponent, multiplication, division, addition, and subtraction.)

2) -3(-x/3)=-3* 2

Lastly, you are going to reduce and simplify your new equation. This last step will achieve you your desired answer.

3) x= -6

User Or Guz
by
5.5k points